2021
DOI: 10.3389/fnana.2021.690168
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regional Loss of Cortical Synapses Lacking Presynaptic Mitochondria in the 5xFAD Mouse Model

Abstract: Synaptic loss in Alzheimer's disease (AD) is strongly correlated with cognitive impairment. Accumulating evidence indicates that amyloid pathology leads to synaptic degeneration and mitochondrial damage in AD. However, it remains unclear whether synapses and presynaptic mitochondria are differentially affected in various cortical regions of the AD brain at the ultrastructural level. Using serial block-face scanning electron microscopy, we assessed synaptic structures in the medial prefrontal cortex (mPFC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Our study thus provided strong support of increased presynaptic mitochondrial damage in AD which is consistent with well documented synaptic mitochondrial dysfunction in the brain of AD patients [ 23 , 28 ]. Furthermore, similar synaptic mitochondrial deficits were reported in cell and animal models of AD [ 32 ]: Aβ treatment of synaptosome caused mitochondrial dysfunction [ 36 ] as well as swollen synaptic mitochondria along with significantly reduced number of SVs [ 45 ]; Significantly reduced presynaptic mitochondria [ 63 ] and increase in presynaptic mitochondria lacking cristae and bioenergetics deficits along with reduced SVs were found in 5xFAD mice [ 2 ]. Mitochondria are strategically localized to presynaptic sites to meet the local needs and the proximity of mitochondria influences synaptic vesicle number [ 67 ].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our study thus provided strong support of increased presynaptic mitochondrial damage in AD which is consistent with well documented synaptic mitochondrial dysfunction in the brain of AD patients [ 23 , 28 ]. Furthermore, similar synaptic mitochondrial deficits were reported in cell and animal models of AD [ 32 ]: Aβ treatment of synaptosome caused mitochondrial dysfunction [ 36 ] as well as swollen synaptic mitochondria along with significantly reduced number of SVs [ 45 ]; Significantly reduced presynaptic mitochondria [ 63 ] and increase in presynaptic mitochondria lacking cristae and bioenergetics deficits along with reduced SVs were found in 5xFAD mice [ 2 ]. Mitochondria are strategically localized to presynaptic sites to meet the local needs and the proximity of mitochondria influences synaptic vesicle number [ 67 ].…”
Section: Discussionmentioning
confidence: 62%
“…It was demonstrated that amyloid-β (Aβ) significantly interfered with mitochondrial dynamics and distribution and caused changes in both presynapse and spines in cell models of AD [ 22 , 56 , 77 , 79 81 ]. Moreover, synaptic mitochondria showed greater alterations and Aβ accumulation [ 22 ] and there was selective regional loss of cortical synapses lacking presynaptic mitochondria in AD mouse models [ 63 ]. While regional loss of mitochondria in presynaptic terminals has also been reported in cortical regions of AD autopsy brain samples [ 49 ], the use of autopsied brain samples limited detailed analysis on synaptic and mitochondrial changes and their relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Since metabolic deregulation in synapses might also account for the deterioration of synaptic plasticity and memory performance (reviewed e.g., [ 71 ]) and there is compelling evidence that metabolic set up of prefrontocortical synapses is modified in animal models of AD [ 72 ], we explored the possibility that alterations of intracellular metabolic coordinators might account for the deterioration of PFC-LTP observed in female APP/PS1 mice. We focused on sirtuins since their levels are reduced in the hippocampus of AD patients [ 17 , 18 ] and animal models [ 19 , 20 ] and their genetic and pharmacological manipulation has been reported to ameliorate several features of AD in animal models [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Uniquely in humans, AD pathology significantly reduces the abundance of specific synaptic proteins (CAMK2 and NPTX2) and neurotrophic factors (BDNF and VGF) [86], a trend which deviates from 5xFAD mouse models in this study. While synaptic loss in 5xFAD mice is well documented; several studies converge to show significant synaptic loss only beyond 4 months of age, none of these studies herein referenced note a decrease in the proteins CAMK2 or NPTX2 specifically [84, 117–121]. Due to the limitations of bulk‐brain proteomics, the microglial‐specific proteomic changes taking place during the transition from MCI to AD in humans or in mouse models of neurodegeneration are currently not known, despite many studies linking complement signaling with synaptic loss and cognitive decline in both mouse and human studies.…”
Section: Insights Into Proteomic Phenotypes Of Microglia From Bulk Br...mentioning
confidence: 99%